The human body & how it works - Royston, Angela, 1945-; Shone, Rob; Forsey, Christopher (New York : Random House, 1991)
Questions and answers introduce the human body and how it works.
"Originally published in Great Britain by Kingfisher Books, a Grisewood & Dempsey Company, in 1990"--T.p. verso.
Includes index.
Keywords: Human physiology -- Juvenile literature; Human anatomy -- Juvenile literature; Human body -- Juvenile literature; Human anatomy -- Miscellanea; Human body -- Miscellanea; Questions and answers